Allostery mapping in enterococcus faecalis Bile Salt Hydrolase (BSH) - Yadav, Yashpal; Ramasamy, Sureshkumar (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: Allostery; Bile salt hydrolase; MD Simulation

Structural insight into self assembly of sophorolipids: a molecular dynamics simulation study - Pandey, Prithvi Raj; Dhasaiyan, Prabhu; Bhagavatula L. V. Prasad; Roy, Sudip (Zeitschrift Fur Physikalische Chemie-International Journal of Research in Physical Chemistry & Chemical Physics, 2016)
Sophorolipids contain hydrophilic head groups at the ends of a long hydrophobic tail. As a result, sophorolipids can self assemble into variety of structures in water. Atomistic self assembly simulations of sophorolipids are performed in water. Two sophorolipids, oleic acid sophorolipid and linolenic acid sophorolipid, differing in number of double bonds in the hydrophobic tail are considered for this study. Long time self assembly simulations are performed considering 1 :3 lipid to water ratio by weight for both oleic and linolenic acid sophorolipids. In addition to 1 : 3 ratio, long time self assembly simulations are also performed with 1 : 1 and 1 : 2 ratios for linolenic acid sophorolipids. Distinctions in structural arrangements of sophorolipid molecules in the self assembled configuration for all the systems are investigated. The present study aims to provide structural insight into the different self assembled configurations of sophorolipids in water.
Keywords: MD Simulation; self assembly; sophorolipids; United Atom Force Field

Functional stability and structural transitions of kallikrein: spectroscopic and molecular dynamics studies - Dalal, Sayli; Mhashal, Anil; Kadoo, Narendra; Gaikwad, Sushama M. (Journal of Biomolecular Structure & Dynamics, 2017)
Kallikrein, a physiologically vital serine protease, was investigated for its functional and conformational transitions during chemical (organic solvents, Gdn-HCl), thermal, and pH induced denaturation using biochemical and biophysical techniques and molecular dynamics (MD) simulations approach. The enzyme was exceptionally stable in isopropanol and ethanol showing 110% and 75% activity, respectively, after 96h, showed moderate tolerance in acetonitrile (45% activity after 72h) and much lower stability in methanol (40% activity after 24h) (all the solvents [90% v/v]). Far UV CD and fluorescence spectra indicated apparent reduction in compactness of KLKp structure in isopropanol system. MD simulation studies of the enzyme in isopropanol revealed (1) minimal deviation of the structure from native state (2) marginal increase in radius of gyration and solvent accessible surface area (SASA) of the protein and the active site, and (3) loss of density barrier at the active site possibly leading to increased accessibility of substrate to catalytic triad as compared to methanol and acetonitrile. Although kallikrein was structurally stable up to 90 degrees C as indicated by secondary structure monitoring, it was functionally stable only up to 45 degrees C, implicating thermolabile active site geometry. In GdnHCl [1.0M], 75% of the activity of KLKp was retained after incubation for 4h, indicating its denaturant tolerance. A molten globule-like structure of KLKp formed at pH 1.0 was more thermostable and exhibited interesting structural transitions in organic solvents. The above results provide deeper understanding of functional and structural stability of the serine proteases at molecular level.
Keywords: isopropanol tolerance; Kallikrein; MD Simulation; Molten globule; Serine protease; Thermostability

Impact of plasticizer addition on molecular properties of polybutadiene rubber and its manifestations to glass transition temperature - Sharma, Pragati; Roy, Sudip; Karimi-Varzaneh, Hossein Ali (Macromolecular Theory and Simulations, 2019)
Effect of blending low and high T-g polymer on the structural, spatial, and temporal properties of the polybutadiene rubber are investigated using molecular dynamics simulations. It is elucidated that smaller chain length counterpart of polybutadiene (5mer-OB) acts as plasticizer for the polybutadiene rubber matrix (32mer-PB). Observed flexibility at macroscopic level by plasticizer addition is corroborated at the molecular level in the form of lower conformational rigidity and faster diffusion of polybutadiene chains in the mixtures. It is inferred that plasticizers decreases T-g of the matrix, due to cooperative influence of decreased chain packing and rigidity. Opposite effect is observed in mixtures with high T-g polymer, polystyrene. T-g of the mixtures showed substantial dependence on the type, concentration, chain length as well as miscibility of plasticizers in the matrix. However, the effect of increasing chain length is more pronounced but counter-controlled by the spatially heterogeneous distribution of the plasticizer. Clustering of polystyrene chains induced significant dynamic heterogeneity in the homogeneous polybutadiene matrix, which apparently lead to reduced plasticization effect. Addition of plasticizers in rubber induce discernible changes in the structural and dynamic properties of the rubber matrix, which manifest as the variation in glass transition and explains the real-life activity of plasticizers.
Keywords: Glass transition temperature; MD Simulation; plasticizer action; polybutadiene rubber; Polystyrene; spatial and dynamic heterogeneity

Transcriptome analysis and Structure-Based drug discovery identifies potential biofungicides for controlling Fusarium wilt in chickpea - Sahoo, Rosaleen; Kadoo, Narendra (Journal of Molecular Liquids, 2024)
Fusarium wilt caused by the fungal pathogen Fusarium oxysporum f.sp. ciceri (Foc) is a devastating chickpea disease. Foc is a soil-borne pathogen that invades plants through roots and can kill them in three to four weeks. Although Fusarium wilt can be controlled by soil solarization or fumigation with chemical fungicides, these are not always effective. Soil fumigation is also hazardous to the beneficial soil microflora, deteriorates soil health, and causes pollution. Hence, there is an urgent need to identify potent and environment-friendly biofungicides to control fungal pathogens. We employed transcriptome analysis and structure-based drug discovery approaches to identify potential biofungicides from four widely used medicinal plants: Lantana camara, Piper betel, Ricinus communis, and Azadirachta indica. Fusarium wilt-resistant and susceptible chickpea varieties were pathogeninoculated and grown under controlled conditions in a greenhouse. Transcriptome analysis was performed to identify pathogenicity-related differentially expressed genes (DEGs). Over 600 phytochemicals from the four medicinal plants and four chemical fungicides were considered for molecular docking against the predicted protein structures of the four most expressed pathogen DEGs. The phytochemicals with the best docking scores and the lowest predicted toxicity risk were considered for molecular dynamics (MD) simulation at 100 ns timescale, and 15 potential biofungicides were identified. This study paves the way for developing biofungicides with enhanced efficacy and safety to manage Fusarium wilt in chickpea.
Keywords: Antifungal molecules; Cicer arietinum; fusarium oxysporum; MD Simulation; medicinal plants; Molecular docking

Integrative multi-omics and computer-aided biofungicide design approach to combat fusarium wilt of chickpea - Sahoo, Rosaleen; Kadoo, Narendra Y. (Planta, 2025)
Main conclusionIntegrating multi-omics and computer-aided drug discovery approaches can overcome the limitations of traditional methods and help develop highly effective, specific, and environmentally safe biofungicides to control crop diseases.AbstractChickpea is a valuable legume crop in terms of nutrition, food security, economic sustainability, and environmental benefits. Fusarium wilt caused by the soil-borne fungus Fusarium oxysporum f.sp. ciceri is one of the most important diseases affecting chickpea. Several disease management methods, including crop rotation, soil fumigation with chemical fungicides, soil solarization, etc., are practiced to manage the disease. However, these methods have various limitations and cannot completely control the disease. Moreover, chemical fungicides indiscriminately kill even the beneficial soil microbes, pollute groundwater, and enter the food chain. Hence, modern approaches emphasizing innovative strategies and technologies need to be explored to manage the disease effectively. In this review, we propose integrating multi-omics (genomics, proteomics, metabolomics, etc.) and computer-aided drug discovery (CADD) approaches to develop biofungicides targeting vital pathogen proteins. Multi-omics approaches can delve deeper into the plant-pathogen interaction and reveal essential pathogen genes or proteins. These proteins could be targeted using CADD to identify phytochemical-based potential biofungicides, either using structure- or ligand-based drug design approaches. The potential biofungicides can be subjected to the prediction of carcinogenicity, hepatotoxicity, mutagenicity, etc., to identify biofungicides that are safe to use and are highly specific to the target pathogen. In vivo and in vitro validation studies can be followed to establish the efficacy and safety of the identified biofungicides for their practical application. This integrated approach can reduce the time and cost compared to the traditional methods and accelerate the discovery of highly effective biofungicides to protect crops from various diseases.
Keywords: CADD; docking; Fungal diseases; MD Simulation; Protein structure prediction; Transcriptomics